Risk perception from the consumption of untreated drinking water in a small island community - Nik Muhammad Nizam Nik Hassan; Paul R. Hunter; Iain R. Lake (IWA Publishing, 2022)
A small island community in Malaysia uses gravity-fed drinking water, and rejected water treatment by the authorities. This study was conducted to evaluate the community's risk perception towards their untreated water supply by interviewing one adult per household in four out of eight villages on the island. The survey asked questions on risk perception, socioeconomic characteristics, and perception of water supply quality. Water samples were collected from a total of 24 sampling locations across the four villages, and 91.7% of them were positive for E.coli. The study surveyed 218 households and found that 61.5% of respondents agreed to some degree that the water is safe to drink without treatment, while 67.9% of respondents disagreed to some degree that drinking tap water is associated with health risks, and 73.3% of respondents agreed to some degree that it is safe to drink directly from taps that are fitted with water filters. Using factor analysis to group the risk perception questions and multivariable GLM to explore relationships with underlying factors, the study found that older respondents, lower income level, positive water odour perception and positive water supply reliability perception lowers risk perception. The village of residence also significantly affects the risk perception level in the model. HIGHLIGHTS Currently there is very little research in Malaysia on drinking water risk perception.; This study is looking at remote community risk perception to help shape water resource management.; This study looks at risk perception of water source and the actual level of faecal indicator.; Finding from this study can be applied to other small and remote community water supplies in the region.;